M6A Modified miR‐31‐5p Suppresses M1 Macrophage Polarization and Autoimmune Dry Eye by Targeting P2RX7 - Lu Zhao; Xuejia Li; Min Gao; Lin Liu; Binyun Ma; Xun Liu; Jiachen Zhang; Ruoxuan Liu; Bei Du; Ruihua Wei; Hong Nian (Advanced Science)
Abstract The dysregulation of the M1/M2 macrophage balance plays a pivotal role in autoimmune diseases. However, the interplay between microRNAs (miRNAs) and N6‐methyladenosine (m6A) modulation in regulating this balance remains poorly understood. Here, a significant reduction in miR‐31‐5p levels is observed in the lacrimal glands of rabbit autoimmune dacryoadenitis and the peripheral blood mononuclear cells (PBMCs) of Sjögren's syndrome (SS) dry eye patients. Overexpression of miR‐31‐5p exhibits preventive and therapeutic effects on rabbit autoimmune dacryoadenitis. Further investigation revealed that miR‐31‐5p overexpression significantly restored the M1/M2 macrophage balance both in vivo and in vitro. Mechanistically, miR‐31‐5p directly targets the P2x7 receptor (P2RX7), leading to the inactivation of p38 mitogen‐activated protein kinases (MAPK) signaling and reduced expression of M1 markers. Furthermore, methylated RNA immunoprecipitation and luciferase reporter assays demonstrated that fat mass and obesity‐associated protein (FTO)‐mediated m6A demethylation, which sustains pri‐miR‐31 stability, is responsible for the decreased miR‐31‐5p levels in autoimmune dry eye. Notably, PBMC samples from SS dry eye patients further support the link between reduced miR‐31‐5p levels and M1 macrophage activation observed in rabbits. Overall, these data highlight the critical role of the FTO/miR‐31‐5p/P2RX7/p38 MAPK axis in autoimmune inflammation, suggesting their potential as therapeutic targets for autoimmune dry eye.